CHARACTERISTICS OF INDICATORS IN PRIVATE CAPITAL VALUATION OF JOINT STOCK COMPANIES IN UZBEKISTAN - Khurshid Kgudoykulov (International Journal of Economic Integration and Regional Competitiveness, 2024)
in the article, the indicators that affect the assessment of the capital value of the joint-stock company are analyzed based on the value of the calculated assets, private capital values from 2015 to 2019. In particular, the main attention is paid to the factors affecting the capital value of joint-stock companies in our country "Kizilkumtsement", "Uzmetkombinat", "Kokon Mechanical Plant" and "Kvarts". Also, the analysis of operating profit after tax NOPLAT and margin NOPLAT indicators of these joint stock companies and return on invested capital (ROIC) coefficients is presented. In turn, existing problems in the evaluation of the capital value of the joint-stock company were identified and scientific proposals and practical recommendations aimed at their elimination were developed